PENGARUH SUHU DAN WAKTU REAKSI PADA PEMBUATAN BIODIESEL DARI MINYAK JELANTAH - Shilvia Vera Sinaga; Agus Haryanto; Sugeng Triyono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
This study aimed to utilize waste cooking oil as raw material for biodiesel production and to study the influence of time and temperature of the transesterification reaction on the biodiesel production and its characteristics.  The study was conducted by base transesterification with NaOH at a molar ratio of waste cooking oil to methanol 1:6.  A combination of three levels of temperature (45⁰C, 55⁰C and 65⁰C) and three levels of reaction time (5 minutes, 10 minutes, and 30 minutes) was performed.  Each treatment was conducted with 3 replications.  The results showed that the yield of biodiesel was affected by temperature and reaction time.  The optimum treatment combination was transesterification at temperature of 65⁰C and 30 minutes of reaction time, which produced 72,87 % methyl ester with a density of 0,85 g/ml, viscosity of 1,65 cSt and acid number of 0,07 %.  Although the density and acid number of biodiesel produced met the biodiesel quality standards of Indonesia (SNI), it was not recommended to be used as fuel engine. Keywords: Biodiesel, waste cooking oil, transesterification, temperature and reaction time.